2013
DOI: 10.1378/chest.12-2414
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Is Associated With an Increased Risk of Respiratory Exacerbations in Patients With Cystic Fibrosis

Abstract: This study demonstrates that exposure to short-term air pollution in a large urban center increases the risk of a pulmonary exacerbation in patients with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 42 publications
(36 reference statements)
0
27
1
5
Order By: Relevance
“…Barometric pressure was found to positively correlate with both O 3 1-h and O 3 8-h in this study, while, in opposition to former research, temperature was negatively associated with ozone concentration [28]. This might be because the months with high temperature were accompanied with high humidity (the rainy season from May to August in Shenzhen), which can influence ultraviolet radiation and thus slow down the formation of ozone.…”
Section: Discussioncontrasting
confidence: 98%
“…Barometric pressure was found to positively correlate with both O 3 1-h and O 3 8-h in this study, while, in opposition to former research, temperature was negatively associated with ozone concentration [28]. This might be because the months with high temperature were accompanied with high humidity (the rainy season from May to August in Shenzhen), which can influence ultraviolet radiation and thus slow down the formation of ozone.…”
Section: Discussioncontrasting
confidence: 98%
“…Over the last 20 years, exposure to fossil fuel combustion has attracted significant medical interest. Many studies have demonstrated that current levels of air pollutants contribute to cardiovascular and respiratory morbidity and mortality in adults and children (2,3,(12)(13)(14). We have analyzed air pollutant measurements in the Sao Paulo metropolitan area over the last 30 years, and observed that pollutant levels recorded at each station were highly correlated with one another.…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, this is a major public health hazard in large cities (2)(3)(4), and children and adolescents are susceptible to the effects of air pollution. However, there are few studies evaluating the association between exposure to air pollutants and autoimmune diseases in this population (4,5), and to our knowledge no study has assessed the influence of air pollutants on the disease activity of juvenile-onset systemic lupus erythematosus (SLE) patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulated AA metabolism has also been shown during CF exacerbations and periods of poor growth, but it has not been linked to SHSe in children with CF 10 11. Although longitudinal studies have shed light on clinical,10 12–14 microbiological15 and environmental16 factors that impact long-term lung disease, modifiable factors such as SHSe and their interaction with immunological, microbiological or AA signalling in infants and young children with CF are relatively unknown.…”
Section: Introductionmentioning
confidence: 99%